2006
DOI: 10.1520/jai13223
|View full text |Cite
|
Sign up to set email alerts
|

European Code of Practice for Creep Crack Initiation and Growth Testing of Industrially Relevant Specimens

Abstract: The integrity and residual life assessment of high temperature components require information obtained from the material's mechanical, uniaxial creep, creep crack initiation (CCI), and growth (CCG) properties. The information derived from these material tests needs to be validated and harmonized following a Code of Practice (CoP) so that variability in data as well as in the analysis can be optimized between different institutions. The paper describes a CoP for creep crack growth testing of industrially releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…4 Components are often welded and the application of the TDFAD approach for weldments has been considered. [12][13][14][15][16] However, a number of complications arise when considering weldments such as material mismatch effects that may require consideration.…”
Section: T D F a D ' S C C I P R E D I C T I O N S I N A U S T E N I mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Components are often welded and the application of the TDFAD approach for weldments has been considered. [12][13][14][15][16] However, a number of complications arise when considering weldments such as material mismatch effects that may require consideration.…”
Section: T D F a D ' S C C I P R E D I C T I O N S I N A U S T E N I mentioning
confidence: 99%
“…The primary and secondary creep constants in Eqs. (14) and (15) are given in Table 1 for 316H stainless steel at 550 • C and P22 steel at 565 • C. For a particular time, the total strain at any stress level is given by the sum of the elastic and plastic strain and the total creep strain accumulated in that time, i.e.…”
Section: Isochronous Stress-strain Datamentioning
confidence: 99%
“…In addition, for the non-steady-state conditions, fracture parameter C t was proposed by Saxena to characterize creep crack growth (CCG). 21,22 And a large number of studies [23][24][25][26][27][28][29] indicated that the CCG rate can be well correlated with C*, which means that C* can be applied to predict and assess creep life of cracked components and devices under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%